Leigh Syndrome: A Rare Mitrochondrial Disorder (Bangladesh Journal of Child Health, 2018)
Leigh syndrome is a rare inherited neurometabolic subacute necrotizing encephalopathy mostly involving brainstem and basal ganglia, seen in the early childhood. It is characterized by progressive loss of mental and motor abilities associated with abnormal muscle tone, weakness, visual loss and respiratory failure. There is no effective treatment for this condition, as such the prognosis of this condition is very bad with death occurring within the first few years of life most commonly due to respiratory failure. Here we present a rare case of Leigh syndrome seen in a 3 and half years male Bangladeshi child with clinical and laboratory features of Leigh Syndrome suggested by neuro-imaging.Bangladesh J Child Health 2017; VOL 41 (3) :189-192